Kärnkraftens värde i framtiden - Bergman, Mårten (2007)
The debate on the future of Nuclear power in Sweden has increased with the discussion on global warming. The uncertainty of fossil fuel- and carbonprices the latest years has aroused considerable interest in Nuclear from power companies, industry and politicians. Nuclear power plants have negligible CO2 emissions and are not directly affected by increased price of emission rights and fossil fuels. The future power production needs to reduce its emissions of greenhouse gases to become sustainable.